SUMOylation of the Kv4.2 Ternary Complex Increases Surface Expression and Current Amplitude by Reducing Internalization in HEK 293 Cells - Welch, Meghyn A.; Jansen, Leslie-Anne R.; Baro, Deborah J. (Frontiers in Molecular Neuroscience, 2021)
Kv4 alpha-subunits exist as ternary complexes (TC) with potassium channel interacting proteins (KChIP) and dipeptidyl peptidase-like proteins (DPLP); multiple ancillary proteins also interact with the alpha-subunits throughout the channel’s lifetime. Dynamic regulation of Kv4.2 protein interactions adapts the transient potassium current, IA, mediated by Kv4 alpha-subunits. Small ubiquitin-like modifier (SUMO) is an 11kD peptide post-translationally added to lysine (K) residues to regulate protein-protein interactions. We previously demonstrated that when expressed in human embryonic kidney (HEK) cells, Kv4.2 can be SUMOylated at two K residues, K437 and K579. SUMOylation at K437 increased surface expression of electrically silent channels while SUMOylation at K579 reduced IA maximal conductance (Gmax) without altering surface expression. KChIP and DPLP subunits are known to modify the pattern of Kv4.2 post-translational decorations and/or their effects. In this study, co-expressing Kv4.2 with KChIP2a and DPP10c altered the effects of enhanced Kv4.2 SUMOylation. First, the effect of enhanced SUMOylation was the same for a TC containing either the wild-type Kv4.2 or the mutant K437R Kv4.2, suggesting that either the experimental manipulation no longer enhanced K437 SUMOylation or K437 SUMOylation no longer influenced Kv4.2 surface expression. Second, instead of decreasing IA Gmax, enhanced SUMOylation at K579 now produced a significant 35-70% increase and a significant 30-50% increase in Kv4.2g surface expression that was accompanied by a 65% reduction in TC internalization. Blocking clathrin-mediated endocytosis (CME) in HEK cells expressing the Kv4.2 TC mimicked and occluded the effect of SUMO on IA Gmax; however, the amount of Kv4.2 associated with the major adaptor for constitutive CME, adaptor protein 2 (AP2), was not SUMO dependent. Thus, SUMOylation reduced Kv4.2 internalization by acting downstream of Kv4.2 recruitment into clathrin coated pits. In sum, the two major findings of this study are: SUMOylation of Kv4.2 at K579 regulates TC internalization most likely by promoting channel recycling. Additionally, there is a reciprocity between Kv4.2 SUMOylation and the Kv4.2 interactome such that SUMOylation regulates the interactome and the interactome influences the pattern and effect of SUMOylation.